2005
DOI: 10.1007/s11167-005-0389-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Chloromethyl-5-aryl-, 2-Chloromethyl-5-(5-methyl-2-furyl)-, and 2-Chloromethyl-5-(1,5-dimethyl-2-pyrrolyl)-1,3,4-oxadiazoles from Tetrazole Derivatives

Abstract: Acetylation of 5-aryltetrazoles, 5-(5-methyl-2-furyl)tetrazole, and 5-(1,5-dimethyl-2-pyrrolyl)tetrazole with chloroacetyl chloride was studied.1,3,4-Oxadiazoles are key fragments of various drugs, from antiviral agents to antidepressants; they are used as organic scintillators and are components of specialty polymerizing formulations, etc.[1].The goal of this study is the development of a onepot procedure for preparing 5-aryl-2-chloromethyl-1,3,4-oxadiazoles and previously unknown 2-chloromethyl-5-(5-methyl-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Tetrazole 89 with chloroacetyl chloride ( 90 ) give disubstituted oxadiazole 91 (Entry a , Scheme 34 ) [ 58 ]. Reflux of 4-methoxyphenyltetrazole ( 92 ) with 4- tert -butylbenzoyl chloride for 2 h affords 2-(4- tert -butylphenyl)-5-(4-methoxyphenyl)-1,3,4-oxadiazole ( 93 ) in 96% yield (Entry b , Scheme 34 ) [ 59 ].…”
Section: Methods Of Synthesis For 25-disubstituted-134-oxadiazomentioning
confidence: 99%
“…Tetrazole 89 with chloroacetyl chloride ( 90 ) give disubstituted oxadiazole 91 (Entry a , Scheme 34 ) [ 58 ]. Reflux of 4-methoxyphenyltetrazole ( 92 ) with 4- tert -butylbenzoyl chloride for 2 h affords 2-(4- tert -butylphenyl)-5-(4-methoxyphenyl)-1,3,4-oxadiazole ( 93 ) in 96% yield (Entry b , Scheme 34 ) [ 59 ].…”
Section: Methods Of Synthesis For 25-disubstituted-134-oxadiazomentioning
confidence: 99%
“…1,3,4-Oxadiazole derivatives were synthesized via the reaction of hydrazide derivatives using different reagents such as CS 2 [47], POCl 3 /aromatic carboxylic acid [48], thionyl chloride [49][50][51], triphenylphosphine oxide, [52] silica-supported dichlorophosphate [53] and ZrCl 4 [54]. The syntheses of 1,3,4-oxadiazoles via the Huisgen reaction [55,56] is a less popular methodology than the methods mentioned above. On the other hand, Efimova et al reported [57] the synthesis of 1,3,4-oxadiazole derivatives via the acylation of tetrazoles with acetic and benzoic anhydrides.…”
Section: (Figure 2) Also N-(5-(cyano(4-methyl-3-phenylthiazol-2(3h)-mentioning
confidence: 99%
“…Experiments [20][21][22] showed that nucleophilic substitution reaction of 5-aryl-2-chloromethyl-1,3,4-oxadiazoles with UDMH produced a series of corresponding chlorides in 64%~84% yield which are all water soluble and biologically active: UDMH involved in the pyrazole cyclization directly in the synthesis process of pyrazole, but it is on the side chain of oxadiazole by nucleophilic substitution reaction in the synthesis of oxadiazoles.…”
Section: B Oxadiazolementioning
confidence: 99%